Sustainable urban electricity supply chain – Indicators of material recovery and energy savings from crystalline silicon photovoltaic panels end-of-life. (November 2018) - Corcelli, Fabiana; Ripa, Maddalena; Leccisi, Enrica; Cigolotti, Viviana; Fiandra, Valeria; Graditi, Giorgio; Sannino, Lucio; Tammaro, Marco; Ulgiati, Sergio
Highlights: The environmental costs of the PV panels end-of-life need to be carefully evaluated. Two end-of-life scenarios for c-Si PV panels are compared by LCA methodology. Thermal treatment of PV panels offers a promising solution for materials recovery. The main environmental benefits arise from the recovery of aluminum and silicon. Abstract: Solar photovoltaic (PV) electricity has the potential to be a major energy solution, sustainably suitable for urban areas of the future. However, although PV technology has been projected as one of the most promising candidates to replace conventional fossil based power plants, the potential disadvantages of the PV panels end-of-life (EoL) have not been thoroughly evaluated. The current challenge concerning PV technology resides in making it more efficient and competitive in comparison with traditional fossil powered plants, without neglecting the appraisal of EoL impacts. Indeed, considering the fast growth of the photovoltaic market, started 30 years ago, the amount of PV waste to be handled and disposed of is expected to grow drastically. Therefore, there is a real need to develop effective and sustainable processes to address the needed recycle of the growing number of decommissioned PV panels. Many laboratory-scale or pilot industrial processes have been developed globally during the years by private companies and public research institutes to demonstrate the real potential offered by the recycling of PV panels. One of the tested up lab-scale recycling processes – for the crystalline silicon technology – is the thermal treatment, aiming at separating PV cells from the glass, through the removal of the EVA (Ethylene Vinyl Acetate) layer. Of course, this treatment may entail that some hazardous components, such as Cd, Pb, and Cr, are released to the environment, therefore calling for very accurate handling. To this aim, the sustainability of a recovery process for EoL crystalline silicon PV panels was investigated by means of Life Cycle Assessment (LCA) indicators. The overall goal of this paper was to compare two different EoL scenarios, by evaluating the environmental advantages of replacing virgin materials with recovered materials with a special focus on the steps and/or components that can be further improved. The results demonstrate that the recovery process has a positive effect in all the analyzed impact categories, in particular in freshwater eutrophication, human toxicity, terrestrial acidification and fossil depletion indicators. The main environmental benefits arise from the recovery of aluminum and silicon. In particular, the recovered silicon from PV waste panels would decrease the need for raw silicon extraction and refining in so lowering the manufacturing costs, and end-of-life management of PV panels. Moreover, the amount of the recovered materials (silicon, aluminum and copper, among others) suggests a potential benefit also under an economic point of view, based on present market prices.